The Influence of Leverage, Total Asset Turnover, Liquidity, and Company Size on Company Financial Performance in Consumer Industry Sector Companies Listed on the Indonesia Stock Exchange 2018-2021 - Andy, Andy; Pratama, Ayang; Lubis, Yeti Meliany (Journal Of Accounting Management Business And International Research, 2023)
This study examined the effect of leverage, total asset turnover, liquidity, and company size on company financial performance in consumer industry sector companies listed on the Indonesia Stock Exchange in 2018-2021. The analytical method used in this research is multiple linear regression with SPSS. Observations of this study using purposive sampling and obtained a sample of 34 companies by testing the classical assumptions, multiple linear regression, hypothesis testing, and the coefficient of determination. The conclusions from the results of this study indicate that partial leverage, total asset turnover, and liquidity significantly affect the Company's financial performance. In contrast, company size does not significantly affect the Company's economic performance. Simultaneously the four factors, namely leverage, total asset turnover, liquidity, and company size, greatly influence the Company's financial performance.